"La censura a mi bloccherebbe": alpine Grenzdynamiken in literarischen Darstellungen des Ersten Weltkriegs - Mehrbrey, Sophia (Romanische Forschungen, 2025)
Building on theoretical approaches from the field of border studies, the paper studies the aesthetics and poetics of borders in literary representations of the Alpine region. The focus is on the restructuring of national borders between Austria and Italy during World War I. In war narratives, - borders take on an intensified significance: both frontier lines and border- scapes are frequently transgressed, deconstructed, and reorganized. This is particularly true for the Dolomite-Front, as border peaks that were difficult to map until the 20th century were suddenly transformed into - brutally contested battle lines. To meet the complexities and ambivalences of bilingual traditions within the Alpine regions, the paper includes novels in Italian and German language. The paper compares Luis Trenker's novel Berge in Flammen (1931) and four contemporary novels to examine - the continuities and discontinuities within the aesthetic representations of cultural, regional, and national border making.
Online veröffentlicht: 1. März 2025
Gesehen am 10.11.2025